Central Composite Design Assisted Formulation Development and Optimization of Gastroretentive Floating Tablets of Dextromethorphan Hydrobromide - Chinthaginjala, Haranath; Abdul Ahad, Hindustan; Kethandapatti Srinivasa, Sainath; Yaparla, Srihith Roy; Buddadasari, Snehitha; Abul Hassan, Junaid; Pullaganti, Sai Sree (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The existing study is concerned with the formulation and optimization of dextromethorphan hydrobromide floating tablets via central composite design. Materials and Methods: Direct compression method was employed to prepare the tablets. Drug -excipient studies were executed through FT-IR and DSC analysis. The independent variables selected were the concentrations of Carbopol 934 (X1) and HPMC K15M (X2). The dependent variables designated were Floating Lag Time (FLT) and Drug Release (DR) at 12 hr. The model was found to be nonlinear and the curvature effect was significant. Hence, the system suggested to central composite design. Results: FT-IR studies demonstrated that there is no considerable interaction amid the drug and the excipients. DSC studies revealed that drug and excipient were compatible as there is no significant alteration in melting point of drug when blended with excipients. The precompression parameters of the formulations showed good flow properties. The evaluation of post compression parameters indicated that all the prepared formulations were within the specified limits. Floating lag time of formulations were marked to be less than 1 min and total floating time exceeding 12 hr. Percentage drug release of all formulations were in the range of 89.7% to 99.4%. The obtained design space/contour plots were used for selecting batches in desirable ranges. Conclusion: The results revealed that experimental design was successfully used to optimize polymer concentrations. It was determined that the central composite design would be used to formulate dextromethorphan gastroretentive floating tablets with fewer trials and higher quality features.
Keywords: Dextromethorphan Hydrobromide; Carbopol; HPMC; Central Composite design; Floating lag time